MANAGEMENT OF LAW ENFORCEMENT ACTIVITIES: THEORETICAL AND LEGAL ASPECT - Kunev, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to analyze and reveal the problems of the theoretical and practical plan regarding the presentation of elements of the activity system for the management of law enforcement activities and the path of development of the legal management of law enforcement activities. Research methods: a comprehensive approach to creating a theoretical picture of the object and applying the methodological scheme of "double knowledge" about the object as such and about the knowledge that describes and depicts it; comparative legal and doctrinal knowledge of the law enforcement management system, as well as the method of generalization and modeling of new theoretical knowledge of legal support of law enforcement activities. Results: the problems of the further development of the theory and practice of management and public law are identified and a theoretical approach to their solution is proposed. It has been established that the management of law enforcement activity is, in essence, activity over activity - management activity over executive activity (law enforcement) and requires activity modeling, for the further creation of legal models for both the management of legal activities in general and the management of law enforcement activities and the legal organization of law enforcement activities and its varieties . Such modeling of the legal organization of law enforcement activities can help to organize a conscious, purposeful process of transition to a new qualitative level, which involves changing the components of law enforcement activities through the formation of new qualities of legislation in the field of law enforcement and filling the functional places of the system of activities for the implementation of legislation. Basic activity schemes for the development of law enforcement activities were also considered. Discussion: the proposition is argued that the practical implementation of approaches based on the construction and implementation of a system of activity models for the management of law enforcement activities are effective for the practical implementation of the needs of increasing the efficiency of legislation formation and implementation of the state’s protective function.